2021
DOI: 10.3389/fimmu.2021.669103
|View full text |Cite
|
Sign up to set email alerts
|

CAR Macrophages for SARS-CoV-2 Immunotherapy

Abstract: Targeted therapeutics for the treatment of coronavirus disease 2019 (COVID-19), especially severe cases, are currently lacking. As macrophages have unique effector functions as a first-line defense against invading pathogens, we genetically armed human macrophages with chimeric antigen receptors (CARs) to reprogram their phagocytic activity against SARS-CoV-2. After investigation of CAR constructs with different intracellular receptor domains, we found that although cytosolic domains from MERTK (CARMERTK) did … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The modules identified various proteins and metabolites involved in inflammatory and vascular injury processes, such as MMP 12, Cathepsin D and RAGE which, to the best of our knowledge, have not yet been studied as targets for therapeutic intervention in COVID-19. Of note, our modules contained IL-6, which is already a mainstay of treatment for severe disease (Brown et al, 2021), and several other molecules such as carnitine, niacinamide and IFN-gamma which others have been studying in the context of COVID-19 therapies (Li et al, 2021;van Laarhoven et al, 2021;Fu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The modules identified various proteins and metabolites involved in inflammatory and vascular injury processes, such as MMP 12, Cathepsin D and RAGE which, to the best of our knowledge, have not yet been studied as targets for therapeutic intervention in COVID-19. Of note, our modules contained IL-6, which is already a mainstay of treatment for severe disease (Brown et al, 2021), and several other molecules such as carnitine, niacinamide and IFN-gamma which others have been studying in the context of COVID-19 therapies (Li et al, 2021;van Laarhoven et al, 2021;Fu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…173 Apart from targeting cancer, CAR macrophages have been tested against SARS-CoV-2 viruses. A recent study by Fu et al 174…”
Section: Macrophagesmentioning
confidence: 95%
“…Human macrophages were engineered with CARs to exhibit anti-tumor potential and, as they are crucial effectors of the innate immune response, it was thought CAR macrophages could be utilised to fight SARS-CoV-2 in a study carried out by Fu et al [85,86]. The limitation of this study resided in the hyperinflammatory macrophage response which could be extremely harmful to the host, specifically those with severe infections, such as SARS-CoV-2 or CRS.…”
Section: Car T/car-nk Cell Therapymentioning
confidence: 99%
“…This work showed that CAR macrophages could serve as promising therapeutics for COVID-19 and that the MERTK-based CAR receptors did not upregulate proinflammatory cytokines. Additionally, direct virion clearance was displayed by CAR macrophages [86].…”
Section: Car T/car-nk Cell Therapymentioning
confidence: 99%